P828 Incidence and predictors of arterial and venous thromboembolic events in hospitalized patients with inflammatory bowel disease compared to patients with acute infective gastroenteritis and colitis: a propensity score-matched study. (30th January 2023) - Papa, A; Lopetuso, L R; Mignini, I; Settanni, C R; Scaldaferri, F; Pugliese, D; Laterza, L; Covino, M; Franceschi, F; Gasbarrini, A
Abstract: Background: Arterial and venous thromboembolic events (ATEs and VTEs) represent a common complication of inflammatory bowel disease (IBD) with significant morbidity and mortality. Risk factors for thromboembolic complications may differ in IBD patients from those in the general population. This study aimed to assess the incidence and risk factors for ATEs and VTEs in a cohort of hospitalized patients with IBD compared to patients with acute infective gastroenteritis or colitis (AIGEC). Methods: The clinical records of patients with IBD and AIGEC admitted to our Academic Hospital over six years were reviewed. We compared the incidence and risk factors of ATEs and VTEs between the two cohorts (1203 patients with IBD and 2652 with AIGEC) and propensity score-matched (PSM) subpopulations, including 831 patients for each group. In addition, we assessed the effect of IBD itself on the occurrence of ATEs and VTEs. Results: In the PSM cohort, the ATEs rate was significantly higher in patients with IBD than in controls (10.1% vs. 5.5%, p=0.001), as well as the incidence of ischemic heart disease (IHD) (7.9% vs. 3.6%, p<0.001). On the contrary, the incidence of VTEs was similar between the two study groups. IBD diagnosis, male sex, hypertension, diabetes, and the Charlson Index were independently associated with ATEs. In patients diagnosed with IBD, the adjusted odds ratio (OR) for an ATE occurrence was 2.21 [1.47 – 3.31] compared to controls. Age emerged as the only factor significantly associated with VTEs. Conclusion: Compared to patients with AIGEC, IBD patients showed an increased risk of ATEs but not VTEs, probably for implementing venous thrombosis prophylaxis. IBD itself represents an independent risk factor for ATEs, particularly for IHD. These findings confirm that chronic inflammation is a consistent trigger for the cardiovascular atherothrombotic disease. Consequently, tight control of inflammation must be considered an essential target to reduce cardiovascular risk.